Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 5 Polynomials and Polynomial Functions - 5.3 Add, Subtract, and Multiply Polynomials - 5.3 Exercises - Skill Practice - Page 350: 51



Work Step by Step

Plugging in the values we get: $B=(2x-3)^2$, hence $V=\frac{1}{3}(2x-3)(2x-3)(3x+4)=\frac{1}{3}(4x^2-6x-6x+9)(3x+4)=\frac{1}{3}(4x^2-12x+9)(3x+4)=\frac{1}{3}(12x^3-36x^2+27x+16x^2-48x+36)=\frac{1}{3}(12x^3-20x^2-21x+36)=4x^3-\frac{20}{3}x^2-7x+12$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.